10 Years of Evaluation Research Into Gaming Simulation for German Entrepreneurship and a New Study on Its Long-Term Effects. (April 2016) - Kriz, Willy C.; Auchter, Eberhard
Background. Over the past ten years, we carried out several comprehensive studies in the area ofentrepreneurship education usingbusiness games that simulate thebusiness processes of startups. The studies researched the learning effects of these games on German university students. Aim. The studies we present investigated if thesimulation game-based educational entrepreneurship programs in Germany reached their goals. These goals included the fostering of participants' entrepreneurial competencies and desire to create a startup. Method. We show traditional summative output-oriented results and more profound results based on ourtheory-based evaluation approach . A so-calledlogic model provides a framework for the interpretation of what takes place during theentrepreneurship business simulations . Currently, we have conducted research on more than 50 regular university courses with more than 1000 students. Another part of our studies is the evaluation ofentrepreneurship education in the German national business game-based competition, EXIST priME Cup (further calledEPC ). More than 12, 000 students attended more than 500 of these cup seminars. We also show new results from an online survey that was carried out to measure the long-term effects of the startupsimulation-based seminars . Results. The results of five studies are summarized, and show an overall increase in the participants' knowledge ofbusiness administration andbusiness plan preparation skills (required in start-up context). Apart from other results, significantgender-based differences are identified. The differences relate toentrepreneurial attitudes and motivation . Some testscenarios with cup seminars for women only with extendeddebriefing seem to reduce this decrease in themotivation of women; further research with larger samples is necessary. A new study on the long-term effects shows a very high acceptance rate and demonstrates the satisfaction of former students. Thesimulation game-based program resulted in participants starting startups at a rate that is approximately twice as high (around 16%) as the normal rate in Germany.